Relationships between muscle mass, strength and regional bone mineral density in young men - Sutter, Thibault (PLoS One, 2019)
PURPOSE: Although the relationship between body composition and bone mineral density (BMD) is well established, the relative contribution of appendicular lean mass (ALM) and fat mass (FM) to BMD has been rarely evaluated in young men. METHODS: We assessed 100 young men (age: 24.4±2.8 years, BMI: 23.4±2.81 kg/m(2)). Appendicular lean mass index (ALM/H(2)) (ALMI), fat mass index (FM/ H(2)) (FMI), percentage of body fat, BMD at lumbar spine (LS), total hip (TH), femoral neck (FN) and whole body (WB) were measured using DXA. Muscle strength was evaluated by handgrip strength. Pearson’s correlations and interactions between all variables were assessed using stepwise regression analyses. RESULTS: ALM index (ALMI) was positively correlated with BMD at all sites (r = 0.62 for WB p<0.05, r = 0.54 for FN p<0.05, r = 0.64 for TH p<0.05, r = 0.56 for LS p<0.05) whereas FMI was not correlated to BMD values. Stepwise regression analyses showed that ALMI produced a significant and positive influence on BMD (β = 0.07 for WB p<0.001, β = 0.04 for FN p<0.001, β = 0.06 for TH p<0.001). Conversely, FMI was negatively associated with BMD at all sites (β = -0.02 for WB p<0.001, β = - 0.03 for FN p<0.001, β = - 0.03 for TH p<0.001, β = - 0.07 for LS p<0.001). Handgrip strength and BMDs were significantly and positively associated at all sites. CONCLUSIONS: Our data suggest that BMD was positively associated with ALMI while negatively with FMI. We confirm that ALMI is the strongest factor associated with BMD in a population of young men.